Hubungan antara Status Gizi dan Kualitas Tidur dengan Kelelahan Kerja pada Pekerja Operator Produksi PT PLN Nusantara Power UP Gresik - Rosmita Rahma Dania; Abdul Rohim Tualeka (Lembaga Pengembangan Kinerja Dosen, 2026)
Work fatigue represents a key occupational health issue that diminishes worker productivity and heightens accident risks. This study aims to examine the relationship between nutritional status, sleep quality, and work fatigue among production operators at PT PLN Nusantara Power UP Gresik. Employing a quantitative approach with an observational analytic design via cross-sectional method, the research included 50 production operators as the population, selected through total sampling. The dependent variable was work fatigue, while nutritional status and sleep quality served as independent variables. Work fatigue was assessed using the Industrial Fatigue Research Committee (IFRC) questionnaire, nutritional status via Body Mass Index (BMI), and sleep quality with the Pittsburgh Sleep Quality Index (PSQI). Data analysis utilized Pearson correlation test on SPSS at α = 0.05. Findings revealed a significant association between nutritional status and work fatigue (p = 0.009; r = 0.364), alongside a strong significant link between sleep quality and work fatigue (p < 0.001; r = 0.686).